The Micropaleontology Collection at the Laboratory of Historical Geology and BioGeosciences (National and Kapodistrian University of Athens, Greece) - Maria Triantaphyllou; Vasiliki-Grigoria Dimou; Elisavet Skampa; Katerina Kouli; Theodora Tsourou; George Kontakiotis; Evangelia Besiou; Margarita Dimiza; Elizabeth Stathopoulou; Hara Drinia; Assimina Antonarakou (Revue de Micropaléontologie, 2026)

Influence of Hydrodynamic Regime on Living Coccolithophores in the Cretan Sea and South Cretan Area (Eastern Mediterranean) - Margarita D. Dimiza; Panagiota Syriopoulou; Elisavet Skampa; Constantine Parinos; Dimitris Velaoras; Pascal Conan; Mireille Pujo-Pay; Angela Maria Oviedo; Xavier Durrieu de Madron; Alexandra Gogou; Maria V. Triantaphyllou (Journal of Marine Science and Engineering, 2026)
Coccolithophores are important components of marine phytoplankton and are found to be useful indicators of the environmental conditions of the upper water column. In this study, we investigate coccolithophore abundance and composition in the Cretan Sea and South Cretan area (Eastern Mediterranean), and their relation to prevailing hydrodynamic conditions during late February/early March 2019. Results showed that total coccolithophore abundance ranged from 26.3 × 102 to 258.8 × 102 coccospheres L−1, averaging at 135.8 × 102 coccospheres L−1. Among the 45 identified species, the opportunistic Emiliania huxleyi was the most dominant, representing 89% of the coccolithophore assemblage. In the Cretan Sea, this species showed relatively homogeneous abundances throughout the upper 100 m depth of the water column; however, towards the Rhodes Cyclone, where a weak stratification had started, and the mixed layer was relatively shallow, higher abundances were found at depths shallower than 50 m. Syracosphaera molischii co-occurred with Emiliania huxleyi, whereas Rhabdosphaera clavigera, Syracosphaera pulchra, and Syracosphaera mediterranea were also present but in lower abundances, reflecting the influence of warm, salty Levantine Surface Water. Based on the morphological analysis, Emiliania huxleyi was mostly represented by heavily calcified forms consistent with winter-spring patterns in the Aegean Sea. The observation of signs of dissolution with high relative abundances of etched/corroded coccospheres indicates the sensitivity of Emiliania huxleyi to the prevailing circulation pattern during the 2019 mixing event within the Rhodes gyre.

Siliceous plankton flux and radiolarian community structure in the highly oligotrophic Ionian Sea (Eastern Mediterranean) – Imprints of climate variability - Marie Cueille; Taniel Danelian; Dimitra-Ioli Skouroliakou; Elisavet Skampa; Maria Triantaphyllou; Alexandra Gogou; Georgia Kambouri; Ioanna Stavrakaki; Koen Sabbe (Marine Micropaleontology, 2025)

A 1-Year Sediment Trap Study on the Downward Flux of Polycyclic Aromatic Hydrocarbons by Settling Particulate Matter in Deep Basins of the Aegean and Ionian Seas, Northeastern Mediterranean - Ester Skylaki; Constantine Parinos; Maria Tsagkaraki; Ioannis Hatzianestis; Anastasia Christidi; Elisavet Skampa; Ioanna Nikolopoulou; Georgia Kambouri; Ioanna Stavrakaki; Dimitris Velaoras; Giorgos Kouvarakis; Maria V. Triantaphyllou; et al. (Journal of Marine Science and Engineering, 2024)
This study investigates the composition, abundance, and vertical export of polycyclic aromatic hydrocarbons (PAHs) across three deep basins of the northeastern Mediterranean Sea (NEMS) over one year. Sinking particles were collected using sediment traps, and PAH analysis was conducted via gas chromatography-mass spectrometry. PAH fluxes varied significantly, peaking in the north Aegean Sea due to mesotrophic conditions, nutrient-rich riverine and Black Sea water inflows, and maritime anthropogenic inputs. The fluxes were highest in winter and lowest in fall. In the Cretan Sea, petrogenic sources (~70%) dominated, driven by currents, with fluxes highest in spring and lowest in winter. The Ionian Sea exhibited lower fluxes, peaking in summer and decreasing in fall. Atmospheric deposition seems to be the main transport pathway of pyrolytic PAHs in this site, while its high-water column depth (4300 m) compared to the other sites presumably enables extended degradation of organic constituents during particle settling. The positive matrix factorization (PMF) and principal component analysis (PCA) results reveal complementary insights into PAH sources and transport mechanisms. PMF analysis identified combustion (61%) and petrogenic (22%) sources, while PCA highlighted biogenic fluxes (57.7%) and atmospheric deposition. Seasonal productivity, riverine inputs, and water circulation shaped PAH variability, linking combustion-related PAHs to atmospheric soot and petrogenic PAHs to organic-rich particles.

Microfacies and species richness analysis of upper Bartonian and Priabonian carbonate shelf deposits from the Thrace Basin (Tethyan Ocean, Greece): Paleoenvironmental evolution and species-richness hotspot revealed - Vasiliki-Grigoria Dimou; Olga Koukousioura; György Less; Maria V. Triantaphyllou; Margarita D. Dimiza; George Syrides; Martin R. Langer (Marine and Petroleum Geology, 2024)

The Contribution of Siliceous Plankton to Vertical Export Flux in the Eastern Mediterranean: A Comparative Study of the North Aegean, Cretan, and Ionian Seas - Ioanna Nikolopoulou; Elisavet Skampa; Ioanna Varkitzi; Margarita D. Dimiza; Constantine Parinos; Georgia Kambouri; Ioanna Stavrakaki; Alexandra Gogou; Maria V. Triantaphyllou (Journal of Marine Science and Engineering, 2024)
This study investigates the intricate dynamics of siliceous plankton species within the open marine regions of the Greek Seas, focusing on their seasonal and spatial variability. For this purpose, vertical export fluxes of diatoms (DtF), silicoflagellates (SF), and radiolaria (RF) were analyzed in three sediment trap time series obtained from the North Aegean, Cretan, and Ionian Seas. Special attention was given to diatom assemblages, resulting in the estimation of the DtF community structure and diversity for each studied site. Diatom flux values reached 353.9 × 103 valves m−2 day−1, 77.7 × 103 valves m−2 day−1, and 42.4 × 103 valves m−2 day−1 in the North Aegean, Ionian, and Cretan Seas, respectively. SF maxima were 1309.8 × 103 skeletons m−2 day−1 in the North Aegean Sea, 35.2 × 103 skeletons m−2 day−1 in the Ionian Sea, and 11.9 × 103 skeletons m−2 day−1 in the Cretan Sea (South Aegean Sea). RF values reached 13.9 × 103 radiolaria m−2 day−1, 11.9 × 103 radiolaria m−2 day−1, and 5.4 × 103 radiolaria m−2 day−1 in the North Aegean, Ionian, and Cretan Seas, respectively. The North Aegean Sea exhibited significantly higher mean total fluxes, particularly for diatoms, driven by the north-to-south oligotrophy gradient, which was influenced by riverine inflows and the nutrient-rich Black Sea water. In the Cretan and Ionian Seas, convective mixing and atmospheric deposition, especially during increased rainfall (precipitation) events, were identified as primary drivers for the increased siliceous plankton fluxes recorded in the late winter–spring months. Diatom communities were dominated by Naviculales and Fragilariales; the prevalence of the former in the North Aegean Sea is likely linked to the higher nutrient levels in its upper photic zone, as Naviculales includes species with a high affiliation to nutrient enrichment.

Nassellarian polycystine radiolarians observed in sediment traps from the southern Ionian Sea (Eastern Mediterranean) - Marie Cueille; Taniel Danelian; Koen Sabbe; Mathias Meunier; Elisavet Skampa; Maria Triantaphyllou; Alexandra Gogou (Revue de Micropaléontologie, 2024)

Humid climate phases on the Island of Rhodes (Greece) during the late Pliocene at times of sapropel formation - Daniela Eichner; Gerhard Schmiedl; Jürgen Titschack; Malu Ferreira; Maria Triantaphyllou; Nils Andersen; Yvonne Milker (Marine Micropaleontology, 2024)

Impact of hydrological changes and vertical motions on Pleistocene marine environments of the eastern coast of the island of Rhodes (Greece) - Daniela Eichner; Gerhard Schmiedl; Jürgen Titschack; Maria Triantaphyllou; Nils Andersen; Nina Forster; Yvonne Milker (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Source rock potential and spatial distribution of the stratigraphic formations in the central Mediterranean Ridge: Evidence from mud volcanic deposits and 2D seismic data - Anastasios Nikitas; Georgios Makrodimitras; Maria V. Triantaphyllou; Nikolaos Pasadakis; Kimon Christanis; Stavros Kalaitzidis; Grigoris Rousakis; Ioannis Panagiotopoulos; Alexandra Gogou; Alexandros Papadopoulos; Efthimios Tartaras; Aristofanis Stefatos (Marine and Petroleum Geology, 2024)

Towards an Integrated and Accurate Planktonic-Foraminiferal-Deduced Bio-Chrono-Stratigraphic Framework of Late Quaternary Mediterranean Marine Cores - George Kontakiotis; Assimina Antonarakou; Evangelia Besiou; Elisavet Skampa; Maria V. Triantaphyllou (Journal of Marine Science and Engineering, 2023)
The late Quaternary is a key stratigraphic interval as it encompasses the Late Glacial to Holocene transition, which is characterized by a series of pronounced centennial climate oscillations and subsequent short-term events of paleoceanographic variability. Across this stratigraphic interval, significant turnovers and faunal changes in the composition and abundance of planktonic foraminiferal assemblages are well-documented through their high-resolution quantitative analysis performed in the south Aegean core NS-18. The identification of 10 synchronous bioevents among the Mediterranean sub-basins allows accurate inter-basinal correlations over the study time interval, thus contributing to the development of a robust chronostratigraphic framework for this setting. Moreover, the identification and timing of additional 20 diachronous bioevents, in conjunction with the already established bio-ecozonation scheme of the Aegean Sea, provide a continuous record of faunal changes (in terms of species-specific distributional abundances) which can be used as an additional locally expressed biochronological tool for the eastern Mediterranean deep-sea cores. The present study certainly indicates that the cause-and-effect relationships between the paleoceanographic/paleoclimatic perturbations and biological response require a highly resolved regional chronostratigraphy.

Phytoplankton and pigment composition during an Emiliania huxleyi bloom in the Black Sea - Elif Eker-Develi; Merve Konucu; Stella Psarra; Natalia Slabakova; Maria Triantaphyllou; Margarita Dimiza; Aristomenis P. Karageorgis; Zahit Uysal; Jean-François Berthon (Regional Studies in Marine Science, 2023)

Seasonal Variability in Present-Day Coccolithophore Fluxes in Deep Eastern Mediterranean Sea: A Multi-Year Study (2015–2017) of Coccolithophore Export in SE Ionian Sea at 4300 m Depth - Sikandar Hayat; Elisavet Skampa; Alexandra Gogou; Spyros Stavrakakis; Constantine Parinos; Maria Triantaphyllou (Journal of Marine Science and Engineering, 2022)
This study is the first attempt to understand the coccolith flux and its seasonal variability at the deepest part of the Mediterranean Sea. Samples were obtained from the deepest Mediterranean time-series sediment trap (4300 m) moored in the SE Ionian Sea (Nestor site) from January 2015 to November 2017. Throughout the study period, the coccolith fluxes displayed a seasonality signal with high values during the late winter–early spring convective mixing period (February to April) and low flux values during summer except for some solitary peaks in June. The maximum coccolith flux was observed in March 2015 while the minimum value was recorded in November 2017. Among the nineteen identified species of heterococcoliths, the dominant species in all the samples was Emiliania huxleyi reaching up to 79%, followed by Florisphaera profunda that comprised up to 33% of the total coccolith count. For the annual cycle of 2015, the average coccolith flux for the Nestor Site at a relatively shallower depth (2000 m) was comparable and for some time intervals was lower than the coccolith flux recorded in the present study at 4300 m, while coccolith flux peaks appeared simultaneously in both traps indicating a fast sinking rate. The higher E. huxleyi, F. profunda, Gladiolithus flabellatus, and Calciosolenia brasiliensis coccolith flux at 4300 m compared with their corresponding fluxes at 2000 m can be attributed to lateral advection, resuspension, and/or the influence of Eastern Mediterranean Deep Waters (EMDWs).

Investigation of the Inherent Variability of the Mediterranean Sea Under Contrasting Extreme Climatic Conditions - Angeliki Sampatakaki; Vassilis Zervakis; Ioannis Mamoutos; Elina Tragou; Alexandra Gogou; Maria Triantaphyllou; Nikolaos Skliris (Frontiers in Marine Science, 2021)
The internal variability of the thermohaline circulation of the Mediterranean Sea is examined under contrasting extreme thermal and mass atmospheric forcing conditions. Three millennium-long numerical simulation experiments were performed under: (a) the current climatology, (b) a strong buoyancy forcing (SBF) scenario due to cold and dry conditions resembling the Younger Dryas event, and (c) a weak buoyancy forcing (WBF) scenario due to S1a sapropel deposition-like conditions (warm and wet). To isolate the inherent variability of the system, independent of interannual atmospheric forcing variability, the latter was defined as a perpetual year pertinent to each experiment. Self-diagnosed heat and salt fluxes, consistent to sea-surface characteristics of the above periods, forced three millenium-long, relaxation-free numerical experiments. These simulations were preceded by initial spin-up periods. The inherent spatiotemporal variability of the Mediterranean Sea was analyzed using the empirical orthogonal function (EOF) and spectral analysis on the simulated density fields. Our results revealed that the Mediterranean Sea exhibits high sensitivity to climatic conditions, allowing its circulation to change from anti-estuarine (for the SBF scenario, leading to a buoyancy loss to the atmosphere) to estuarine (for the WBF scenario, corresponding to a buoyancy gain from the atmosphere). In all three experiments, the interannual and decennial variabilities dominate in upper layers, and the decennial variability dominates in the Gibraltar and Sicily Straits. Under current climatic conditions the first two EOF modes express only 60% of the density variability in the deep layers. This contribution exceeds 90% under more extreme conditions. Moreover, the first EOF modes correspond to a basin-wide in-phase variability of the deep layers under the reference and WBF conditions. During SBF conditions the first modes reveal a vertical buoyancy exchange between upper and deeper layers. The second EOF mode of deep waters under both extreme scenarios showed that the western and eastern basins exchange buoyancy in decennial (for the cold/dry) and interdecennial (for the warm/humid) timescales. The residence time of the Eastern Mediterranean deep water was diagnosed to be centennial, semicentennial, and intercentennial for the cases of current period, SBF, and WBF, respectively.

Phytoplankton community structure changes during autumn and spring in response to environmental variables in Methana, Saronikos Gulf, Greece - Pierros Patoucheas; Olga Koukousioura; Stella Psarra; Katerina Aligizaki; Margarita D. Dimiza; Elisavet Skampa; Ioannis Michailidis; Paraskevi Nomikou; Maria V. Triantaphyllou (Environmental Science and Pollution Research, 2021)

Community responses of intertidal foraminifera to pH variations: a culture experiment with propagules - Anna E. Weinmann; Susan T. Goldstein; Maria V. Triantaphyllou; Martin R. Langer (Aquatic Ecology, 2021)

Luminescence geochronology and paleoenvironmental implications of coastal deposits of southeast Cyprus - Evangelos Tsakalos; Constantin Athanassas; Polychronis Tsipas; Maria Triantaphyllou; Maria Geraga; George Papatheodorou; Eleni Filippaki; John Christodoulakis; Maria Kazantzaki (Archaeological and Anthropological Sciences, 2018)

Holocene Climatic Optimum centennial-scale paleoceanography in the NE Aegean (Mediterranean Sea) - Maria V. Triantaphyllou; Alexandra Gogou; Margarita D. Dimiza; Sofia Kostopoulou; Constantine Parinos; Grigoris Roussakis; Maria Geraga; Ioanna Bouloubassi; Dominik Fleitmann; Vassilis Zervakis; Dimitris Velaoras; Antonia Diamantopoulou; et al. (Geo-Marine Letters, 2016)

Corrigendum: A well‐established Early–Middle Pleistocene marine sequence on south‐east Zakynthos island, western Greece: magneto‐biostratigraphic constraints and palaeoclimatic implications - Maria D. Papanikolaou; Maria V. Triantaphyllou; Ellen S. Platzman; Philip L. Gibbard; Conall Mac Niocaill; Martin J. Head (Journal of Quaternary Science, 2011)

A well‐established Early–Middle Pleistocene marine sequence on south‐east Zakynthos island, western Greece: Magneto‐biostratigraphic constraints and palaeoclimatic implications - Maria D. Papanikolaou; Maria V. Triantaphyllou; Ellen S. Platzman; Philip L. Gibbard; Conall Mac Niocaill; Martin J. Head (Journal of Quaternary Science, 2011)
The chronostratigraphy of a long, onshore Early–Middle Pleistocene marine sedimentary sequence on the south‐east part of Zakynthos island, Greece, is presented. Correlation of the succession with the isotope record of Ocean Drilling Program Site 963 reveals the combined influence of tectonics and eustacy in this area. The sequence is divided into three formations by two main unconformities that apparently relate to sea‐level lowstands associated with two major northern hemisphere glaciations, those of marine isotope stages (MIS) 22 and 12. The Zakynthos sequence in many ways is comparable with the Italian Valle di Manche section. Magnetostratigraphic and rock magnetic analyses, supported by biostratigraphy, document the position of the Matuyama/Brunhes Chron boundary (0.77 Ma), the top and base of the Jaramillo Subchron (0.99–1.07 Ma), the Cobb Mountain Subchron (1.173–1.185 Ma) and the top of the Olduvai Subchron (1.78 Ma). The underlying strata are constrained exclusively by detailed nannofossil biostratigraphy extending at least to the lowermost Pleistocene at around 2.54 Ma and therefore certainly incorporating the base of the Olduvai Subchron (1.95 Ma) and possibly the Gauss/Matuyama Chron boundary (2.58 Ma). In addition, a remarkable increase in sedimentation rate (from 3.2 and 28 cm ka −1 to 167 cm ka −1 ) and hence resolution above the Matuyama/Brunhes boundary (Middle Pleistocene) reveals one short‐lived magnetic excursion, possibly 17a (0.66 Ma), within the normal polarity Brunhes Chron. Copyright © 2011 John Wiley & Sons, Ltd.

Calcareous nannofossil and planktonic foraminiferal distributional patterns during deposition of sapropels S6, S5 and S1 in the Libyan Sea (Eastern Mediterranean) - Maria V. Triantaphyllou; Assimina Antonarakou; Margarita Dimiza; Christos Anagnostou (Geo-Marine Letters, 2010)